2013
DOI: 10.1089/ten.teb.2011.0678
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Need for Regenerative Therapies: Translation-Focused Analysis of U.S. Regenerative Medicine Opportunities in Cardiovascular and Peripheral Vascular Medicine Using Detailed Incidence Data

Abstract: Cardiac and vascular diseases represent one of the most substantial medical areas for the applications of regenerative medicine. Despite advances in endovascular repair, surgical intervention, and disease management, atherosclerosis and heart failure continue to be prominent health problems. This report analyzes the regenerative medicine treatment opportunities in both cardiovascular and peripheral vascular repair, examining the treatment opportunities for tissue-engineered vascular grafts as well as cell-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A recent study suggested that even though CABG procedures are more common, peripheral artery revascularizations and AVFs for vascular access demonstrated stronger commercial feasibility as the initial target market for the TEVG in the clinic. 279 It is also likely that in the future of healthcare, cost/benefit will not be the only justification for a new medical technology such as the TEVG. Demonstrating value to the patient and medical system is also likely to become a more important factor.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that even though CABG procedures are more common, peripheral artery revascularizations and AVFs for vascular access demonstrated stronger commercial feasibility as the initial target market for the TEVG in the clinic. 279 It is also likely that in the future of healthcare, cost/benefit will not be the only justification for a new medical technology such as the TEVG. Demonstrating value to the patient and medical system is also likely to become a more important factor.…”
Section: Discussionmentioning
confidence: 99%
“…The surgeons anastomose the graft with a healthy vessel and reconnect the blood flow downstream. A vascular bypass is a common surgical procedure for limb salvage following critical limb ischemia and various peripheral vascular diseases associated with diabetes, atherosclerosis, or aging, and is a prevailing therapeutic option for coronary artery diseases [1]. Vascular prostheses are also essential for arteriovenous fistulae, hemodialysis vascular access, and large vessel reconstruction-linked congenital defects or aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…For applications, such as peripheral and coronary bypasses that require small diameter grafts, the benchmark vascular grafts are autologous, including the internal mammary artery, the radial artery from the arm, and the saphenous vein from the leg [1]. Although very successful in a majority of patients, the lack of natural grafts is a concern for approximately 30% of those who need multiple grafts or have vascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Damaged myocardium cannot be restored on its own as native cardiomyocytes are limited in regenerative abilities. Hence, cardiac tissue engineering aims to provide biological solutions to restore the ill-function-A ing heart and has the largest potential in regenerative medicine [7] . A potential medical solution is through injecting cells at infarct site or via intracoronary route [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering is a field which applies the principles of engineering and life sciences to develop biological substitutes that can restore, maintain or improve tissue function [16] . Specifically, cardiac tissue engineering aims to provide biological solutions to restore failing hearts and has one of the largest potential in regenerative medicine [17] . With advancement of three-dimensional (3D) printing, also known as additive manufacturing, various techniques have been applied in producing patientspecific biological substitutes, ranging from orthopedic implants [18][19] to scaffolds for tissue engineering [14,20] .…”
Section: Introductionmentioning
confidence: 99%